Clinical Outcomes After Liver Transplantation in Patients With Portopulmonary Hypertension. Issue 10 (October 2021) - Cartin-Ceba, Rodrigo; Burger, Charles; Swanson, Karen; Vargas, Hugo; Aqel, Bashar; Keaveny, Andrew P.; Heimbach, Julie; Taner, Timucin; Nyberg, Scott; Rosen, Charles; Cajigas, Hector; DuBrock, Hilary; et al.
Abstract : Background: Portopulmonary hypertension (POPH) is the presence of pulmonary arterial (PA) hypertension in patients with portal hypertension and is associated with significant morbidity and mortality. In a cohort of POPH patients, we describe the clinical outcomes of POPH patients who underwent liver transplantation (LT). Methods: Retrospectively collected data from a prospectively assembled cohort of all consecutive POPH adults evaluated in 3 transplant centers from 1996 to 2019. Results: From a cohort of 228 POPH patients, 50 patients underwent LT. Significant hemodynamic improvement after PA-targeted therapy was observed, with 58% receiving only monotherapy pretransplant. After LT, 21 (42%) patients were able to discontinue and remained off PA-targeted therapy. The 1-, 3-, and 5-y unadjusted survival rates after LT were 72%, 63%, and 60%, respectively. An elevated pulmonary vascular resistance (PVR) before LT was associated with worse survival rate (HR, 1.91; 95% CI, 1.07-3.74, P = 0.04). No survival difference was observed in those granted MELD exception or transplants performed before or after the year 2010. Conclusions: Significant number of POPH patients discontinued PA-targeted therapy after LT. Higher PVR before LT was associated with worse survival, as was monotherapy use. Despite effective PA-targeted therapies, POPH survival outcomes after LT in our cohort were modest and may reflect the need for more aggressive therapy.